Pedagogika porównawcza jako obszar budowania podmiotowości sprawczej przyszłych pedagogów - Tołwińska, Bożena (Wydawnictwo Naukowe UAM, 2016)
The article includes the development of the thesis that the analysis carried out in the framework of comparative education, as a discipline dealing with the phenomenon of education in the broad context, showing the "entanglement education" 1, often they provide students an important source of reflection and a kind of "discovery" of what they experience, but can not be called. Knowledge and understanding of the impact of a number of conditions for the development of education, in particular the political and economic although it is only a precondition, may encourage the development of a sense of agency and taking intentional actions aimed positive bottom-up change in the environment of human life.
Comparative Education as the Area of Creating Future Teachers' Agency
Keywords: higher education; university; comparative education; agency